Improving the physical condition of students influenced by jogging - Серорез [Tetiana Serorez] Тетяна Борисівна; Мершавка [Valetyna Mershavka] Валентина Миколаївна (Slobozhanskyi Herald of Science and Sport, 2013)
The article is devoted the problem of increase of level of bodily condition of student young people by the different modes of the running trainings. The results of research of influence of the running trainings are presented in the aerobic and mixed modes energy supply on the aerobic and anaerobic productivity of the organism. It is set that efficiency of trainings depends on the mode of energy supply of work and power inputs. Research of influence of the running trainings of the different sending to the aerobic and anaerobic (lactates) productivity of organism witnessed advantages of the running loadings which stimulate the anaerobic processes of energy supply. The presence of close cross-correlation connections is confirmed between the aerobic and anaerobic (lactates) productivity of organism and endurance which grounds consideration last as one of basic components of physical health. It is set that connection by the aerobic and anaerobic (lactates) productivity of organism with other high-quality parameters of motive activity weak or absent.